Pooled in vitro and in vivo CRISPR-Cas9 screening identifies tumor suppressors in human colon organoids - Michels, Birgitta E.; Mosa, Mohammed H.; Streibl, Barbara I.; Zhan, Tianzuo; Menche, Constantin; Abou-El-Ardat, Khalil; Darvishi, Tahmineh; Członka, Ewelina; Wagner, Sebastian; Winter, Jan; Medyouf, Hind; Boutros, Michael; et al. (Cell stem cell, 2020)
Colorectal cancer (CRC) is characterized by prominent genetic and phenotypic heterogeneity between patients. To facilitate high-throughput genetic testing and functional identification of tumor drivers, we developed a platform for pooled CRISPR-Cas9 screening in human colon organoids. Using transforming growth factor β (TGF-β) resistance as a paradigm to establish sensitivity and scalability in vitro, we identified optimal conditions and strict guide RNA (gRNA) requirements for screening in 3D organoids. We then screened a pan-cancer tumor suppressor gene (TSG) library in pre-malignant organoids with APC−/−;KRASG12D mutations, which were xenografted to study clonal advantages in context of a complex tumor microenvironment. We identified TGFBR2 as the most prevalent TSG, followed by known and previously uncharacterized mediators of CRC growth. gRNAs were validated in a secondary screen using unique molecular identifiers (UMIs) to adjust for clonal drift and to distinguish clone size and abundance. Together, these findings highlight a powerful organoid-based platform for pooled CRISPR-Cas9 screening for patient-specific functional genomics.
Gesehen am 10.06.2020